Respect - Bullis, Amber (Minneapolis, MN : Jump!, 2021)
"In this book, readers will learn what respect is, how and why to show it, how to use mindfulness to better practice respect, and how to encourage it in others. Social and emotional learning (SEL) concepts support growth mindset throughout, while Grow with Goals and Writing Reflection activities further reinforce the content. Vibrant, full-color photos and carefully leveled text engage young readers as they learn more about showing respect. Also includes sidebars, a table of contents, glossary, index, and tips for educators and caregivers"--
What is respect? -- Respecting others -- Self-respect -- Grow with goals -- Mindfulness exercise.
Includes index.
108693
Keywords: Respect -- Juvenile literature; Values; Juvenile works